Enhanced Recovery Pathway Benefits Patients Undergoing Nonelective Colorectal Surgery. Issue 4 (April 2021) - Liska, David; Novello, Matteo; Cengiz, Bora Turgut; Holubar, Stefan D.; Aiello, Alexandra; Gorgun, Emre; Steele, Scott R.; Delaney, Conor P.
Abstract : Objective: The aim of our study was to determine if an enhanced recovery pathway (ERP) can successfully be applied in nonelective colorectal surgery. Background: ERPs have been shown to reduce hospital length of stay (LOS), complications, and costs after elective colorectal surgery. Yet, little data exist regarding the benefits of ERPs in patients undergoing nonelective colorectal surgery. We hypothesized that ERP implementation in a nonelective colorectal surgery population is associated with decreased postoperative LOS. Methods: A prospectively-maintained database was used to identify consecutive patients undergoing colorectal surgery after emergency room (ER) or hospital transfer admissions over a period from 2 years before until 1 year after implementation of a comprehensive ERP. The primary endpoint was LOS. Secondary endpoints included total LOS [TLOS = postoperative LOS + LOS of readmission(s)], readmission rates, complication rates, 30-day mortality, and hospital costs. Univariate and multivariate analyses were performed to assess the relationship between ERP implementation and LOS. Results: We identified 269 pre-ERP and 135 ERP patients fulfilling the inclusion criteria. Admit source (ER 43.4% vs transfers 56.7%), Charlson comorbidity index, American Society of Anesthesiologists (ASA) status, diagnosis (inflammatory bowel disease 45.8%, malignancy 19.6%, benign intestinal obstructions 10.4%, diverticulitis 9.4%, others 10.4%), and blood loss were comparable ( P > 0.05) between the cohorts. Pre-ERP patients had a higher number of previous abdominal surgeries, whereas post-ERP patients had more laparoscopy and more compliance with ERP elements. ERP patients had a shorter postoperative LOS [6 (4, 10) vs 7 (5, 12) days; P = 0.0007]. Hospital costs were 13.4% lower ( P = 0.004). Postoperative 30-day morbidity, mortality, and readmissions were comparable, although reoperation rate was higher in the ERP group. On multivariate analysis, ERP implementation and laparoscopy were the only modifiable variables independently associated with shorter LOS, whereas longer operative times and higher ASA classification were associated with longer LOS. Conclusions: Patients undergoing nonelective colorectal surgery after ER or hospital transfer admission benefit from the use of an ERP, demonstrating decreased LOS and costs without an increase in complications.